(untitled) (Research, Society and Development, 2021)
This study evaluated the prediction of contamination of water resources by pesticides in the Pindaré river basin, in the municipality of João Lisboa (Maranhão), using the mathematical models of EPA, GUS and GOSS. The results showed that 40,0% of pesticides applied by farmers on crops are at risk of reaching water resources. The active principles aminopilaride, fluroxypyr, picloram and triclopyr were considered as potential groundwater contaminants. With this, it is recommended that the use of these active ingredients should be avoided or the substitution of others with less mobility promoted, with a view to environmental protection.